Pengaturan Pemberian Hak Upah Dalam Proses Pemutusan Hubungan Kerja dan Implementasinya Dalam Putusan Hakim - Dian Ekawati; Dadan Herdiana (Jurnal Kewarganegaraan, 2023)
Abstract This research aims to analyze the regulation of wage entitlements in the process of employment termination and their implementation in judge's decisions. The research question is "How is the regulation of wage entitlements in the process of employment termination governed by labor laws and regulations, and how is it implemented in judge's decisions?" The research adopts a literature review method with a normative juridical analysis approach. The data used consist of laws, regulations, Supreme Court decisions, and Constitutional Court decisions. The analysis involves identifying legal provisions that govern wage entitlements in the process of employment termination, examining the interpretations given by the Supreme Court in its decisions, and comparing these regulations with Constitutional Court decisions and other applicable regulations. The findings indicate that the regulation of wage entitlements in the process of employment termination is not specifically addressed in labor laws and regulations. This lack of clarity leads to varying interpretations and implementations by the Supreme Court in its decisions. To achieve consistency, the Supreme Court has issued Circular Letter No. 3 of 2015, which stipulates that employers are required to pay process wages for a period of six months following Constitutional Court Decision No. 37/PUU-IX/2011. This aims to reduce the parties' responsibility for delays in the Industrial Relations Court process. The research emphasizes the importance for relevant parties, including employers and workers, to pay attention to the latest laws and legal decisions related to wage entitlements in the process of employment termination. Consistent implementation and adherence to applicable regulations will help maintain uniformity, clarity, and fair protection of the rights of workers and employers in accordance with the prevailing legal provisions. Keywords: Wage Entitlements, Employment Termination, Legal Regulation, Judge's Decisions, Normative Juridical Analysis.